2010
DOI: 10.1172/jci42542
|View full text |Cite
|
Sign up to set email alerts
|

Gankyrin plays an essential role in Ras-induced tumorigenesis through regulation of the RhoA/ROCK pathway in mammalian cells

Abstract: Activating mutations in Ras proteins are present in about 30% of human cancers. Despite tremendous progress in the study of Ras oncogenes, many aspects of the molecular mechanisms underlying Ras-induced tumorigenesis remain unknown. Through proteomics analysis, we previously found that the protein Gankyrin, a known oncoprotein in hepatocellular carcinoma, was upregulated during Ras-mediated transformation, although the functional consequences of this were not clear. Here we present evidence that Gankyrin plays… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
66
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(66 citation statements)
references
References 60 publications
0
66
0
Order By: Relevance
“…We previously reported that Gankyrin is overexpressed in human lung and breast cancers and plays an essential role in breast cancer metastasis (10,16). To determine the role of Gankyrin in tumor metastasis, we extended our observation to CRC given that Gankyrin promoted cell proliferation and tumor growth in a colon cancer cell line HCT116 as recently reported (33).…”
Section: Elevated Gankyrin Expression In Primary Colorectal Cancers Wmentioning
confidence: 58%
See 1 more Smart Citation
“…We previously reported that Gankyrin is overexpressed in human lung and breast cancers and plays an essential role in breast cancer metastasis (10,16). To determine the role of Gankyrin in tumor metastasis, we extended our observation to CRC given that Gankyrin promoted cell proliferation and tumor growth in a colon cancer cell line HCT116 as recently reported (33).…”
Section: Elevated Gankyrin Expression In Primary Colorectal Cancers Wmentioning
confidence: 58%
“…(iv) Overexpression of Gankyrin prevents nuclear translocation of NF-kB subunit and inhibits the transcriptional activity of NF-kB (2). (v) Gankyrin mediates Ras-induced tumorigenesis by suppressing ROCK activity (16), and (vi) Gankyrin enhances PI3K/AKT/HIFa signaling pathway in hepatocellular carcinoma (HCC; refs. [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Many of these dysregulated genes are known to exhibit altered expression in HCC and, in some cases, functionally contribute to hepatocarcinogenesis. Such genes include components of insulin-like growth factor 2 (Igf2), Ras, and β-catenin (Ctnnb1) signaling pathways (Supplemental Figure 4A), as well as other genes known to play a role in HCC such as Epcam (21), c-Myc (23), and Rhoa (24). Real-time RT-PCR validated the upregulation of several of these transcripts in LKO livers ( Figure 2E and Supplemental Table 4), and Western blotting documented the increased expression of the majority of these proteins in KO livers ( Figure 2F).…”
Section: Liver-specific (Lko) and Germline (Ko) Mir122 Loss Of Functimentioning
confidence: 99%
“…111 In addition, several reports showed that Gankyrin-mediated liver cancer includes activation of PI3K/Akt pathway and Rho/ROCK/PTEN signalling. 112,113 Interestingly, the activation of some of these pathways correlates with expression of stemness factors. 114 Although elevation of Gankyrin in HCC is well documented, very little is known about mechanisms by which liver cancer activates Gankyrin.…”
Section: Signalingmentioning
confidence: 99%